HAEMATOLOGICAL INDICES AND SERUM BIOCHEMISTRY OF BROILER CHICKEN FINISHER FED DIETS CONTAINING DRIED AVOCADO PEAR SEED (Persea americana) - Akinduro, Victor Olabisi (Journal of Agricultural Sciences (Belgrade), 2021)
ABSTRACT The general acceptability of plants with proven records of medicinal values in the tropics in recent time, necessitated the use of dried Avocado pear in broiler diet and its possible effects on haematological variables and biochemical indices, the study focused on haematological and biochemical responses of broilers to varying level of inclusion of dried avocado pear seed. The inclusion levels were 0% of the dried Avocado pear seed as control, 2.5%, 3.5%, 4.5% and 5.5%. The experiment lasted for eight weeks, four weeks for the starter phase (for acclimatization of the birds and maturation of their GIT) and four weeks for the test trials (finisher phase). The result showed that there were significant differences (P<0.05) in the haematological parameters, which implied that the inclusion of the dried Avocado pear seed in broilers’ diet had a positive influence on platelet, lymphocytes, monocytes, eosinophils and heterophils. The presence of lymphocytes was an indication of adequate production of antibodies and which could prevent opportunistic infections as was observed during the experimental trials with birds without the test ingredients. The dried Avocado pear seed had a positive influence on Aspartate aminotransferase (AST), Albumin (ALB), Total protein (TP), Triglyceride and High Density Lipoprotein (HDL). It could be concluded from this study that Avocado pear seed has significant effects on improving the haematological and serum characteristics of broiler birds with the highest value recorded in T4 (4.5%) and T5 (5.5%).